Efforts to Improve Student Learning Outcomes Using Picture Media and Activity Sheets in Islamic Education Learning at SD Negeri No. 104294 Pematang Setrak - Jusmaita; Suheri (DARUSSALAM: Scientific Journal of Islamic Education, 2024)
This research aims to improve student learning outcomes in worship materials through the use of picture media and activity sheets in grade V of Elementary School. The background of this research is the low learning outcomes and the lack of interest of students in worship materials in Islamic Religious Education learning. This can be seen from the low evaluation score and the lack of student activity in the learning process. Therefore, an interesting and fun approach is needed so that students can more easily understand the material presented. The method used in this study is Class Action Research (CAR) which is carried out in two cycles. Each cycle consists of the stages of planning, implementation of actions, observation, and reflection. The subjects in this study are grade V students at one of the State Elementary School No. 104294 Pematang Setrak, with a total of 25 students. Data collection techniques include observation of student activities, learning outcome tests, and documentation of learning activities. The results of the study showed an increase in student involvement in the learning process, characterized by increased student activity in discussions, answering questions, and completing assignments in activity sheets. The average score of student learning outcomes has also increased from cycle I to cycle II. This shows that the use of attractive picture media and interactive activity sheets can increase students' understanding of worship materials. Thus, this strategy can be used as an alternative in improving the quality of Islamic Religious Education learning, especially in worship materials in class V.